A plant volatile‐based attractant formulation is not attractive to Diadegma semiclausum (Hymenoptera: Ichneumonidae). Issue 3 (28th June 2017) - Yazdani, Maryam; Baker, Greg
Abstract: A synthetic plant volatile‐based attractant has been commercialised for integrated pest management (IPM) of Helicoverpa armigera (Hübner) and H. punctigera (Wallengren) in Australian cotton, corn and beans. This attract‐and‐kill formulation is being tested in Australia in canola as an IPM tool to minimise the amount of insecticide used for the control of diamondback moth (DBM) Plutella xylostella (Linnaeus). DBM is a destructive insect pest of cruciferous crops with a cosmopolitan distribution and has developed resistance to almost every synthetic insecticide applied in the field. However, in brassica crops, naturally occurring parasitoids are often important components of IPM. Therefore, it is essential to investigate how parasitoids deal with plant volatiles released from this formulation and whether this formulation is safe for non‐target insects especially parasitoids. Wind tunnel experiments were conducted to assess the effect of the formulation on larval parasitoid Diadegma semiclausum (Hellén), which is an effective biological control agent of DBM. Our results showed that the formulation was significantly less attractive than either water or untreated leaves. Unfed female D. semiclausum were highly attracted to the honey food source, while after feeding, there was no significant preference among treatments with the exception of significantly less visits to leaves treated with the formulation. Furthermore, the presence of the formulation appears to have reduced the attractiveness of leaves, which were infested with DBM larvae. Our result shows that 2 days after application, female wasps visited leaves treated with the formulation significantly less than untreated healthy leaves, even if DBM larvae were present on the leaves treated with the formulation. We conclude that the formulation is not attractive to D. semiclausum female wasps. The wasps' avoidance of leaves treated with the attractant, even if those leaves were infested with DBM larvae, suggests that the formulation can act as a repellent to the female wasps.